LEGAL CONFLICTS IN THE SYSTEM OF STATE AWARDS OF VOLUNTEERS PROVIDING VOLUNTEER ASSISTANCE TO THE ARMED FORCES OF UKRAINE - Drobina, Inna; Prokhorenko, Mykhailo (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The principal objective of the article is the analysis of the legal conflicts in the system of granting the awards to the volunteers, who provide the volunteering assistance to the Armed Forces of Ukraine. In particular, the article defines the decisive factors of the legal conflict as well as the way of their elimination. The research methods: the methodological base relies on the general scientific methods and special juridical methods. These methods enabled the authors to investigate the problem of the national system of state awards, particularly the encouragement of volunteers who provide support to the Armed Forces of Ukraine. Results: the development of the theoretical provisions is considered as the result of this article. They become the basis for the substantiation of the necessity to divide the state awards into the so-called «military» and «civil» in order to avoid the hybridization of the legal statuses of both awards and their cavaliers. Besides, the authors proposed to amend the statutes of the state awards, approved by the decree of the President of Ukraine «On the establishment of the distinction by the President of Ukraine – «The Order for Bravery» on 21 August 1996 № 720/96, «On the establishment of the distinction by the President of Ukraine – «The Order for Merit» on 22 September 1996 № 870/96, «On the establishment of the distinction of the President of Ukraine – «The Order of Princess Olga» on 15 August 1997 № 827/97. Discussion: article examines the generally accepted practice of awarding the volunteers who provide support to the Armed Forces of Ukraine that is not directly stipulated in the regulatory documents. It necessitates the further scientific inquiry as for the reformatting of the system of awards and the revision of the statutes of some state awards in order to bring them into the compliance to the Law of Ukraine «On state awards», as well as the development of clear criteria for awarding and encouraging the people who provide the volunteer and charitable assistance to the Armed Forces of Ukraine.